2010
DOI: 10.1007/s10147-009-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of dihydropyrimidine dehydrogenase and thymidylate synthase expression in patients with pancreatic cancer

Abstract: The efficacy of 5-FU may be lower in pancreatic cancer tissue than in normal tissue because DPD activity is upregulated in pancreatic cancer tissue compared to normal pancreatic tissue. It is necessary to develop an effective 5-FU delivery system and/or 5-FU combined with an inhibitor for DPD that can be used when 5-FU must be administered to patients with pancreatic cancer. High DPD activity may be a prognostic factor in patients with pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Therefore, inhibition of GSK3b may sensitize pancreatic cancer cells to gemcitabine via sequential modification of the Rb/E2F pathway. It was recently reported that TS, a target of E2F transcription and fluoropyrimidine-derived chemotherapeutic agents, is frequently activated in primary pancreatic cancer tissues [46]. This suggests that inhibition of GSK3b also sensitizes pancreatic cancer cells to fluoropyrimidines, such as 5-fluorouracil and S-1, which are prescribed for patients with advanced and/or recurrent pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibition of GSK3b may sensitize pancreatic cancer cells to gemcitabine via sequential modification of the Rb/E2F pathway. It was recently reported that TS, a target of E2F transcription and fluoropyrimidine-derived chemotherapeutic agents, is frequently activated in primary pancreatic cancer tissues [46]. This suggests that inhibition of GSK3b also sensitizes pancreatic cancer cells to fluoropyrimidines, such as 5-fluorouracil and S-1, which are prescribed for patients with advanced and/or recurrent pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the eligible studies are summarized in Table I. A total of 5 studies (9)(10)(11)13,19), published between 2002 and 2012, met the inclusion criteria for this review. A total of 425 patients were subjected to the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, conflicting results have been reported from various laboratories. Besides its predictive value, the reported findings on the expression levels and prognostic value of TS are also inconsistent (9)(10)(11)(12)(13). Therefore, a meta-analysis was performed to assess the prognostic value of TS protein expression for the survival of patients with pancreatic adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Although conflicting results have been reported, [19][20][21][22] Tsuji et al 10 reported that DPD low was significantly associated with reduced RFS in stage II to stage III colorectal cancers treated with surgery alone.…”
Section: Discussionmentioning
confidence: 99%